Hubungan Kadar Soluble FMS-Like Tyrosine Kinase 1 (sFlt-1) Ibu Preeklampsia Dengan Berat Badan Lahir Bayi - Sabrin, Gusriani; Sunardi, Wahida; Noviyanti, Nur Indah (-)
Soluble Fms like tyrosine kinase 1 (sFlt-1) is one of the markers that play a role in the pathogenesis of pregnancy induced hypertension. The aims of the research were to determine the relationship beteween sFlt-1 level and birth weight. The samples were preeclampsia inpartu consisting of 22 peopole,, and normal pregnancy women consisting of 18 people. Analytic observational study with cross sectional was conducted. The level of sFlt-1 was examined using ELISA. Statistic analysis used Kruskal Wallis test, One way Anova test and Pearson correlation test.The result indicate that the characteristics of research subject in preeclampsia group and control group do not have a significant difference (p>0.05).The negative linear relationship occured between sFlt-1 level with birth weight in preeclampsia (p=0,015). While, in the group of normal pregnancy was not available of the relationship either sFlt-1 level with birth weight (p>0.05).